Analisis Finansial Usaha Pembenihan Ikan Patin (Studi Kasus: UPR Mina Sepakat Jaya Kecamatan Tenayan Raya Kota Pekanbaru Provinsi Riau) - Putri Kusuma Wardani; Hendrik; Trisla Warningsih (Jurusan Sosial Ekonomi Perikanan, 2021)
This research was conducted in Januari 2019 in UPR Mina Sepakat Jaya Tenayan Raya District, Pekanbaru City, Riau Province. This research aimed to determine the amount of investment needed and to analysis the financial feasibility of UPR Mina Sepakat Jaya in Tenayan Raya District, Pekanbaru City, Riau Province. The method used is a case studyand determining the respondents using the census method. The result showed that the initial investment needed in catfish hatchery business in UPR Mina Sepakat Jaya about IDR 101.920.000,- – IDR 112.216.000,-. This catfish hatchery business is feasible to proceed based on range of RCR value from 2,91 to 3,33, on FRR value >bank interest rate, and PPC ranged from 0,9 to 1,1.